Three new species of the free-living nematode genus Oncholaimus Dujardin, 1845 (Enoplida, Oncholaimidae) from Atlantic coasts of Argentina - Pastor, Catalina Teresa (2013)
Three new species of the genus Oncholaimus are described from coastal Patagonia in the Argentinian provinces of Río Negro, Chubut and Santa Cruz. Oncholaimus rionegrensis sp. n. is characterized by males having a precloacal sexual protuberance bearing two fine tubular organs, three short setae on each side in front of the cloacal opening, two pairs of subventral setae located at both sides of the cloacal opening, a large ventro-median protuberance near the tail tip, and spicules with distal cuticular reinforcement. Oncholaimus madrynensis sp. n. is distinguishable by males having a precloacal ovoid plate, a precloacal sexual protuberance bearing two small precloacal supplementary tubular organs and two small setae on both sides, four pairs of long setae in pericloacal position, a huge postcloacal sexual protuberance, and two pairs of subventral papillae on tail. And Oncholaimus deseadensis sp. n. is characterized by the morphology of its precloacal area having one pair of short setae, one short seta, two tubular organs and one pair of setae on each side, and the presence of one postcloacal sexual protuberance bearing a pair of setae on it.